Female playwrights and eighteenth century comedy - Anderson, Misty G. (Palgrave, 2002)
Aphra Behn, Susannah Centlivre, Hannah Cowley, and Elizabeth Inchbald were the only four women in England who enjoyed career-long success as comic playwrights from 1670-1800. Their respective approaches to the body, contracts, nationalism, and divorce animate their comedies and provide comic comment on the marriage plot. By attending to the dialogue between humorous comic events and the more predictable comic endings of these plays, Anderson illuminates the philosophical, political, and legal arguments about women and marriage that fascinated both female playwrights and the theatergoing public.
Keywords: Centlivre; Susannah; Cowley; Hannah; Behn; Aphra; Inchbald; Elizabeth; Engels; Hofmakerij; Huwelijk; Toneelschrijvers; Toneelstukken; Vrouwelijke auteurs; Vrouwen; Drama; Englisch; Frau; Geschichte; Schriftstellerin; Courtship in literature; English drama (Comedy); English drama; Marriage in literature; Theater; Women and literature; Women in literature; Komödie; Dramatikerin; Ehe